Ragna crimson. 3 - Kobayashi, Daiki (Manga artist) (Square Enix Manga & Books, 2021)
"Ragna and Crimson infiltrate the royal city of Celesviera in order to strike down the Winged Monarch, Ultimatia. Crimson summons his followers, Golem and Chimera, in order to devise a plan of attack. Meanwhile, Ragna is wandering the city alone and ends up in a chance encounter with Ultimatia! As he faces off against the time-controlling Winged Monarch, he makes a fateful choice..."--